Pengaruh Program Posyandu Terpadu terhadap Status Gizi Balita di Daerah Pedesaan : Studi Kasus di Desa Sandik, Lombok Barat - Syarif Rahman Hakim; Siti Nurlaela (Journal of Applied Health Sciences, 2025)
Nutritional problems among children under five remain a major public health challenge in rural areas, including Lombok Barat. The Integrated Health Post (Posyandu Terpadu) serves as a strategic government program focusing on monitoring child growth and nutritional status through basic health services at the village level. This study aims to analyze the effect of the Integrated Health Post program on the nutritional status of children under five in Sandik Village, Lombok Barat. A quantitative approach with a cross-sectional design was employed. The study sample consisted of 120 children aged 6–59 months, selected using purposive sampling based on their participation in Posyandu activities. Data were collected through anthropometric measurements (weight, height, and indices W/A, H/A, and W/H) and structured interviews with mothers. The findings revealed a significant difference in the nutritional status of children who regularly attended the Integrated Health Post compared to those who rarely attended (p < 0.05). Regular attendees showed an improvement of 21.7% in achieving normal nutritional status compared to the non-regular group. These results indicate that the Integrated Health Post program plays a vital role in improving child nutrition in rural communities, particularly through growth monitoring and nutrition education for parents. In conclusion, the sustainability and optimization of Integrated Health Post activities are essential strategies for preventing malnutrition and stunting in rural areas.